2018
DOI: 10.1002/er.4073
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on voltage response to operation parameters of a unitized regenerative fuel cell during mode switching from fuel cell to electrolysis cell

Abstract: Summary In this work, a proton exchange membrane unitized regenerative fuel cell with a 25 cm2 active area and a transparent window was designed to study the influence of mode switching from the fuel cell mode to the electrolysis cell mode on the cell voltage and the gas‐liquid two‐phase flow behaviors in the oxygen flow channels. Results indicate that: the growth rate of electrolysis cell voltage before the water pumped to the oxygen flow channels decreases with the increase of the fuel cell current density; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
(25 reference statements)
2
8
0
Order By: Relevance
“…This is because the effect of mass transfer along width direction of porous payers cannot be described based on a two‐dimensional model. Noticed that the reduction of the electric performance of the cell switching to EC mode is similar with experimental results in the study of Li, Hang, Ye, and Ma. In experiments, a long water supply tube results in water supply untimely and thus results in a slight reduction of the cell performance.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This is because the effect of mass transfer along width direction of porous payers cannot be described based on a two‐dimensional model. Noticed that the reduction of the electric performance of the cell switching to EC mode is similar with experimental results in the study of Li, Hang, Ye, and Ma. In experiments, a long water supply tube results in water supply untimely and thus results in a slight reduction of the cell performance.…”
Section: Resultssupporting
confidence: 85%
“…An experimental investigation showed that a slight decline of the electric performance occurs in practical operation of a lab-scaled URFC. 18 The authors suggested that untimely water supply results in water starvation, thereby, causes a slight reduction of the voltage. Over experiment, the advantage of numerical simulation is capable to forecast the species and heat distributions within the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [14] titanium felts with a high specific surface area are researched for regenerative fuel cells with acidic media. In [15] a unitized regenerative PEM fuel cell was researched during switching form fuel cell to electrolysis mode while water has been pumped into the oxygen gas channels. It was figured out that the rate of the two-phase volume flow and the water temperature have a big influence on a temporary voltage peak.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of gas-liquid two-phase flow in URFC is important in cell performance. Excessive liquid water easily causes water flooding and seriously hinders the normal operation of URFC due to the existence of gas and liquid in the cell during the actual operation [18][19][20][21][22][23] . Therefore, studying two-phase flow in simulation and reducing flooding phenomenon is important.…”
Section: Introductionmentioning
confidence: 99%